PENGARUH UKURAN PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN : Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Mutiara Azisah; Agus Endro Suwarno (Jurnal Bina Bangsa Ekonomika, 2024)
Company value is a public assessment of the company's performance results as seen from the share price of companies that experience demand and supply in the capital market. The value of the company will be used as a measure of the success of a company's management so that it can increase trust for shareholders. This study aims to determine the influence of company size, ownership structure, and company growth on company value. The population in this study is manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used the purposive sampling method according to the criteria that had been determined and 96 samples were obtained. However, 5 samples are outliers, so that the final total of samples after outliers is 91 samples that can be used in the study. The data analysis method used is a multiple linear regression analysis model. The results of the study show that managerial ownership and institutional ownership have an effect on the company's value. Meanwhile, the size of the company and the growth of the company have no effect on the value of the company